Rekomendasi Kebijakan untuk Pengelolaan Sampah Kota Padang Berbasis Pengelolaan Komunal dan Terintegrasi - Durain Parmanoan; Aldri Frinaldi; Anni Faridah; Erianjoni Erianjoni; Indang Dewata; Nasfryzal Carlo; Fajar Agung Mulia; Kuntum Khoiro Ummatin; Izzati Winda Murti; Dwi Annisa Fithry (Jurnal Pembangunan Nagari, 2026)
Waste management in Padang City is currently facing a critical phase with the Air Dingin Landfill predicted to reach full capacity in 2026 and having a worrying Environmental Risk Index (IRL). This problem is exacerbated by a large fiscal shortfall, where the regional budget allocation is far less than the ideal requirement of IDR 133 billion per year. This study aims to evaluate the effectiveness of waste policies and formulate a communal-based integrated management strategy as a sustainable solution. The research method uses a qualitative approach through literature studies, a review of Regional Regulation Number 21 of 2012 and flagship government programs such as “Padang Bagoro” and “Padang Mamilah”, as well as secondary data analysis of waste management data (SIPSN). The results of the analysis indicate a functional gap between seasonal social participation and low sorting behavior at source, as well as weak law enforcement due to limited supervisory personnel. This study recommends policy restructuring through a communal-scale management approach (RT-RW) that maximizes communal management and integration with the sub-district Waste Management Institution (LPS) and industrial sector to reduce the logistical burden and extend the technical life of the landfill.